Development displacement and disparity: India in the last quarter of the twentieth century - Banerjee, Nirmala (ed.); Marjit, Sugata (ed.) (New Delhi, 2005)
Development, Displacement and Disparity: The last quarter of the twentieth century. The book is a collection of essays that tackle a crucial theme in developmental economics and planning. The essays: - look at the inequities and disparities of national resource distribution, and the need for a more equitable distribution of national developmental gains reflect a growing concern with many economic theorists over uneven regional development and the need for these issues to be looked at seriously, with a view to attend to them in the best possible ways are on the one hand a theoretical exposition of the economics of public goods supply, but on the other, they point to the lag between theoretical and academic understanding and practical initiative study the areas, evaluate the models of development and suggest new areas of research in development planning.
Keywords: Economic development